Can we conquer unemployment? The Liberal party, public works and the 1931 political crisis1. Issue 239 (13th April 2014) - Sloman, Peter
Abstract David Lloyd George's 1929 pledge to 'conquer unemployment' through loan‐financed public works was a landmark in the development of Keynesianism as a policy option in Britain, yet just two years later the Liberal party which Lloyd George had led would play a central role in the formation of the highly orthodox National Government. This article uses archival and published sources to explain the shift in Liberal thinking, and argues that the party's early interest in reflationary policies was not so much insincere as under‐theorized. Liberal confidence in the value of public works was consequently eroded after 1929 by rising unemployment and the onset of financial crisis.